Relatório de Estágio em Auditoria - da Expetativa à Realidade - Tavares, Eduardo José Durão (2022)
This report follows the curricular internship in the company CFA - Cravo, Fortes e Antão & associados sroc, Lda. for a period of six months, with the aim of obtaining a master's degree in auditing. The work carried out during the internship period is presented, covering most of the auditing process and, in a more in-depth manner, the tests carried out on the work charts adopted by the host entity, in various areas. Scientific articles relevant to the theme in question were analysed, as well as books and regulations. Regarding the structure of this report, the theme is initially approached through a theoretical aspect of conceptual and normative nature concerning the area of auditing. Subsequently, all the activities developed during the curricular internship are addressed and described. Through the completion of this report, it was possible to understand the audit tests carried out and addressed in practical terms during the curricular internship, establishing links between the theoretical and practical aspects, as well as to understand the extent of the audit procedures and the use of tests that the auditor deems necessary to resort to throughout his work. It was thus concluded that the work carried out throughout the auditing process is laborious, sometimes demanding the auditor's professional judgment. First, a good knowledge of the entity to be audited, as well as of the sector in which it operates, is undoubtedly a vital requirement, which in a certain way will shape a large part of the auditor's work. Furthermore, the legislation and all other diplomas which regulate the work to be carried out by the auditor, until he gives his opinion on what he has tested, are varied and consistent in terms of their content.